A new field test to estimate the aerobic and anaerobic thresholds and maximum parameters. Issue 4 (20th April 2020) - Giovanelli, Nicola; Scaini, Stefano; Billat, Veronique; Lazzer, Stefano
Abstract: Evaluation of cardiorespiratory parameters is important in athletic population in order to monitor the training status and define training intensities. The aim of this study was to validate an easy-to-perform running test called RABIT ® (Running Advisor Billat Training) for detecting aerobic (AerT) and anaerobic (AnT) threshold and maximum parameters. Fifteen trained runners completed a graded (GRAD) and RABIT test (four self-selected pace steps: (i) 10 minutes at free warm-up pace, (ii) 5 minutes at medium pace, (iii) 3 minutes at hard pace, (iv) 10 minutes at easy pace). We compared the cardiorespiratory parameters and running speed of the RABIT with those corresponding to AerT, AnT or maximum parameters obtained by the GRAD. The ⩒O2 max, HRmax, RERmax and running speed max measured during the 3-minute hard pace of the RABIT were not statistically different from the maximum parameters measured during GRAD ( p  > 0.05). The ⩒O2, HR and RER measured during the medium and easy pace of the RABIT were not significantly different from the AnT and AerT parameters measured during GRAD. In conclusion, RABIT was validated for all the maximum parameters and for most of Ant- and AerT-related parameters and then it might be used for detecting training zones in athletes.